Modelling user trust and mobile payment adoption: A conceptual framework - Uchenna Cyril., Eze; Gerald Goh Guan, Gan; John, Ademu; Samson A., Tella (2008)
The proliferation of new technologies and the changing dynamics of industry competition have spurred growth in innovative production, marketing and consumption. The need for convenience has also fuelled enormous interest in the use of mobile payment innovations, which in turn creates security challenges for users. Indications are that mobile phones and handheld devices should have made more inroads in businesses and societies as in most advanced societies are at today [1]. Instead, there has been a slow acceptance of mobile and handheld devices as alternative payment systems, especially in developing countries, despite the efforts of key players such as banks, mobile network operators, and mobile payment service providers (MPSP). This paper, therefore, is a conceptual design to examine security factors influencing the acceptance of mobile payment systems in Malaysia. This paper will examine the impact of security dimensions on trust and how these impacts on trust influence users' intention to use mobile payment systems. We will also highlight several research, practitioner and policy implications.